Pemidanaan Bagi Pelaku Tindak Pidana Penganiayaan Biasa - Nurhafifah Nurhafifah; Reza Pahlevi (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
violence or persecution is a problem that always arises in the midst of society. Legally the criminal acts of persecution have been regulated in Article 351 paragraph (1) of the Criminal Code (KUHP), with a maximum imprisonment of up to 2 years. The purpose of this study is to explain the factors causing the occurrence of criminal acts of persecution, as well as the efforts taken in order to cope with the occurrence of criminal acts of ordinary persecution. Data in this study were obtained through library research and field research. The results showed that the factors causing the occurrence of criminal acts of persecution are the nature of emotions or heartaches caused by a dispute. Efforts taken in order to overcome the occurrence of criminal acts of persecution are usually done with repressive efforts. This action can be seen as a precaution for the future so that ordinary perpetrators of criminal offenses do not repeat the crime (recidivist)